Comparison of Long-Term Outcomes Between Repeated Hepatic Resection and Radiofrequency Ablation in Patients with Small Recurrent Hepatocellular Carcinoma After Initial Curative Resection: A Propensity Score Matched Study - Hsiao CY; Hu RH; Liang PC; Wu CH (Journal of Hepatocellular Carcinoma)
Chih-Yang Hsiao,1,2 Rey-Heng Hu,1 Po-Chin Liang,3 Chih-Horng Wu4– 6 1Department of Surgery, National Taiwan University Hospital, Taipei, Taiwan; 2Department of Traumatology, National Taiwan University Hospital, Taipei, Taiwan; 3Department of Medical Imaging, National Taiwan University Hospital, Hsin-Chu Branch, Hsin-Chu, Taiwan; 4Department of Medical Imaging and Radiology, National Taiwan University Hospital and College of Medicine, Taipei, Taiwan; 5Hepatitis Research Center, National Taiwan University Hospital, Taipei, Taiwan; 6Center of Minimal-Invasive Interventional Radiology, National Taiwan University Hospital, Taipei, TaiwanCorrespondence: Chih-Horng Wu, Department of Medical Imaging and Radiology, National Taiwan University Hospital and College of Medicine, 7 Chung-Shan South Road, Zhongzheng District, Taipei, Taiwan, Tel +886 2 2312-3456 Ext.62570, Email chw1020@ntuh.gov.twBackground: Repeat hepatic resection (re-resection) and radiofrequency ablation (RFA) are both standard treatments for small recurrent hepatocellular carcinoma (HCC) after curative resection. This study compares long-term outcomes of these treatments.Methods: This retrospective study included patients with recurrent HCC smaller than 3 cm treated with re-resection or RFA from 2001 to 2019 in a tertiary center. Propensity score matching (PSM) minimized baseline differences. Primary outcomes were overall survival (OS) and disease-free survival (DFS). Subgroup analyses explored outcomes based on recurrence interval, hepatitis infection status, and RFA guidance method (ultrasound [US] versus computed tomography [CT]). Multivariate Cox regression identified predictors of survival and secondary recurrence.Results: After PSM, 106 patients in the re-resection group and 106 in the RFA group were compared. OS rates at 3, 5, and 8 years for re-resection were 97.9%, 85.4%, and 75.8%, compared to 87.8%, 77.9%, and 62.8% for RFA (p = 0.15). DFS rates were 53.3%, 41.8%, and 26.7% for re-resection versus 43.9%, 28.1%, and 24.0% for RFA (p = 0.15). Subgroup analysis indicated re-resection was superior in early recurrence (< 24 months) and HBV-related HCC. US-guided and CT-guided RFA showed no significant differences in OS or DFS. HCV infection and multiple tumors were independent predictors of secondary recurrence.Conclusion: Repeat hepatic resection and RFA offer comparable survival for small recurrent HCC. Re-resection is preferred for early recurrence and HBV-related HCC. US- and CT-guided RFA are equally effective alternatives. Keywords: hepatocellular carcinoma, outcome, radiofrequency ablation, recurrence, repeat resection